Purification and Characterization of Bromelain from Pineapple Variety Josapine - ABD HALIM, MUHAMMAD YAZID; Zainal Abidin, Siti Aimi Sarah; AB MUTALIB, SITI ROHA (Malaysian Journal of Science, 2025)
Pineapple (Ananas comosus (L) Merr) is a plant that contains bromelain enzymes in almost all parts of the plant, such as fruit, leaves, crown, and the stem with different amounts. Bromelain is included in the protease enzyme group that can break down the molecular structure of proteins into amino acids. Pineapple peel is one of the waste products from pineapple processing that has not been used optimally. This study aimed to purify and characterize bromelain enzyme from pineapple variety Josapine peel. The production of bromelain powder in this study was done in four steps, the extraction of crude bromelain from pineapple peel extracts, the purification of bromelain using ammonium sulphate precipitation, desalting using the diafiltration process and finally, freeze drying using a freeze dryer. The protease activity was determine using casein digestion unit (CDU) meanwhile the protein content was determine using Lowry’s Method. Result showed that the highest bromelain activity was observed in maturity index 5 in powder form with 2132.78±18.01 CDU/ml, the highest protein content was observed in maturity index 5 in crude extract form with 4.19±0.17 mg/ml and the highest specific enzyme activity was observed in maturity index 5 in powder form with 15234.14 CDU/mg protein. The agroindustry waste product, Josapine pineapple peel, has potential as a future alternative bromelain source.